2017
DOI: 10.1371/journal.pone.0175678
|View full text |Cite
|
Sign up to set email alerts
|

Relative predictive value of lung cancer screening CT versus myocardial perfusion attenuation correction CT in the evaluation of coronary calcium

Abstract: Coronary artery calcium scores (CACS) from lung cancer screening computed tomography (LCSCT) or myocardial perfusion attenuation correction computed tomography (ACCT) are not routinely performed or reported. CACS from LCSCT and ACCT have not been directly compared in the same patient population. We identified 66 patients who underwent both LCSCT (non-gated) and ECG-gated cardiac CT (CCT) within a 2-year span. Of this population, 40 subjects had also undergone ACCT. Using the Agatston method, CACS for 264 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The results of the study demonstrated that an automatic CCS scoring from AC combined with a fast-visual quality control of the calcific region may allow routine CAD risk assessment. The same threshold was applied by Bailey et al ( 2017 ). They identified 40 patients in an elevated risk population who underwent lung cancer screening computed tomography (non-gated) (LCS-CT), CCS, and AC-CT within the same 2-year period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study demonstrated that an automatic CCS scoring from AC combined with a fast-visual quality control of the calcific region may allow routine CAD risk assessment. The same threshold was applied by Bailey et al ( 2017 ). They identified 40 patients in an elevated risk population who underwent lung cancer screening computed tomography (non-gated) (LCS-CT), CCS, and AC-CT within the same 2-year period.…”
Section: Introductionmentioning
confidence: 99%
“…Larger slices thickness than the standard (3 mm) lead to significantly reduced scoring results with the opposite found using thinner slices (Christensen et al 2019 ) where soft kernels are recommended in CCS (Sprem et al 2018 ). Looking at the outperformance of the LCS-CT in the study by Bailey et al ( 2017 ), despite the intrinsic limitation, so long as appropriate an acquisition has been made it can be reasonable having two reconstructions from a single AC-CCS study, one for the AC, using 5 mm thickness and the full SFOV, and one for CCS, using a 2.5–3 mm slice thickness and a maximum DFOV of 400 mm, as used for LCS-CT.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature search, a total of 4000 patients from 16 studies were included in this meta-analysis [ 12 13 14 16 17 18 19 20 21 28 29 30 31 32 33 34 ]. Table 1 summarizes the study characteristics, CAC scoring method, and technical considerations for the non-ECG-gated CT scans.…”
Section: Resultsmentioning
confidence: 99%
“…The same slice thickness (2.5 or 3 mm) was used for non-ECG-gated CT in 9 studies [ 12 13 14 19 29 30 31 32 34 ]. Different slice thicknesses were used in 8 studies: thinner slices (≤ 2 mm) in 3 studies [ 12 17 28 ] and thicker slices (5 mm) in 5 studies [ 12 14 16 21 33 ]. The studies that used the same slice thickness had higher correlation coefficients and weighted kappa than studies that used different slice thicknesses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation